Prospective Life Cycle Assessment and economic analysis of direct recycling of end-of-life reverse osmosis membranes based on Geographic Information Systems. (1st February 2021) - Senán-Salinas, Jorge; Blanco, Alberto; García-Pacheco, Raquel; Landaburu-Aguirre, Junkal; García-Calvo, Eloy
Abstract: By 2025, the desalination sector will generate two million end-of-life (EoL) spiral-wound reverse osmosis (RO) modules per year. Direct recycling into nanofiltration and ultrafiltration appears as an alternative solution to approach RO membrane technology to the Circular Economy (CE). The present study aims at evaluating the environmental and economic potential of different EoL RO direct recycling strategies at full scale. Therefore, a virtual recycling facility and its supply were projected in a case study assessed by Geographic information systems (GIS) within the Segura's watershed (SWS). The region accumulates 42% of the Spanish desalination capacity. The Life Cycle Assessment (LCA) was referred to one recycled module at the secondary enduser location (functional unit). The system boundaries included the processes from the EoL-RO modules collection to the delivery of recycled products at the secondary endusers location. Nonetheless, it was mainly focused on the transport impact and the EoL-RO modules characterisation. Five ILCD-midpoint categories were analysed. Service Life Ratio (SLR) indicator was also assessed. LCA and SLR results pointed out an important potential environmental benefit of the recycling. The distribution of recycled modules had no relevance within regional and national scales. However, long hauls (>3100 km) could be limited by their contribution to climate change (GWP). Otherwise, membrane modules characterisation was evidenced as a limiting process for closest distributions by its contribution to Human Toxicity (HT-nc). A competitive recycled product selling price of 80 euro per module can be achieved with improvements in the characterisation techniques. Highlights: GIS-LCA provided reliability in the ex-ante logistics quantification. Environmental and economic results evidenced the potential viability of recycling. Transport of recycled modules should be limited within an international scale. Service Life Ratio identified the priority processes for eco-improvement. Economic viability is linked to improvements in waste characterisation.